Mechanical Ventilation Exacerbates Poly (I:C) Induced Acute Lung Injury: Central Role for Caspase-11 and Gut-Lung Axis - Jin, Shuqing; Ding, Xibing; Yang, Chenxuan; Li, Wenbo; Deng, Meihong; Liao, Hong; Lv, Xin; Pitt, Bruce R.; Billiar, Timothy R.; Zhang, Li-Ming; Li, Quan (Frontiers in Immunology, 2021)
Background: The mechanisms by which moderate tidal volume ventilation (MTV) exacerbates preexisting lung injury are unclear. We hypothesized that systemic endotoxemia via the gut-lung axis would lead to non-canonical and canonical inflammasome activation and pyroptosis in a two-hit model involving polyinosinic-polycytidylic acid (Poly(I:C)), a synthetic analog of dsRNA and MTV and that this would associate with acute lung injury (ALI). Methods: Anesthetized mice were administered Poly(I:C) intratracheally and then 6 h later, they were mechanically ventilated for 4 h with otherwise non-injurious MTV (10ml/kg). Changes in intestinal and alveolar capillary permeability were measured. Further documentation of ALI was assessed by evans blue albumin permeability, protein and IL-1 family concentration in bronchoalveolar lavage fluid (BALF) or plasma, and histopathology in cohorts of wildtype (WT), whole body genetically ablated caspase-11 (caspase-11-/-), caspase-1/caspase-11 double knockout (caspase-1/11-/-), gasdermin D (GSDMD)-/-, nucleotide-binding domain leucine-rich repeat-containing protein 3 (NLRP3)-/- and advanced glycosylation end product-specific receptor (RAGE) -/- mice. Results: Non-injurious MTV exacerbated the mild lung injury associated with Poly(I:C) administration. This included the disruption of alveolar-capillary barrier and increased levels of interleukin (IL)-6, high mobility group proteins 1 (HMGB-1), IL-1β in BALF and IL-18 in plasma. Combined (Poly(I:C)-MTV) injury was associated with increase in gastrointestinal permeability and endotoxin in plasma and BALF. Poly(I:C)-MTV injury was sensitive to caspase-11 deletion with no further contribution of caspase-1 except for maturation and release of IL-18 (that itself was sensitive to deletion of NLRP3). Combined injury led to large increases in caspase-1 and caspase-11. Genetic ablation of GSDMD attenuated alveolar-capillary disruption and release of cytokines in combined injury model. Conclusions: The previously noted exacerbation of mild Poly(I:C)-induced ALI by otherwise non-injurious MTV is associated with an increase in gut permeability resulting in systemic endotoxemia. The gut-lung axis resulted in activation of pulmonary non-canonical (cytosolic mediated caspase-11 activation) and canonical (caspase-1) inflammasome (NLRP3) mediated ALI in this two-hit model resulting in GSDMD sensitive alveolar capillary barrier disruption, pyroptosis (alveolar macrophages) and cytokine maturation and release (IL-1β; IL-18). Pharmacologic strategies aimed at disrupting communication between gut and lung, inhibition of inflammasomes or GSDMD in pyroptosis may be useful in ALI.